Effects of the number of players and game type constraints on heart rate, rating of perceived exertion, and technical actions of small-sided soccer games - Abrantes, C. I.; Nunes, M. I.; Macas, V. M.; Leite, N. M.; Sampaio, J. E. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to identify the variation of heart rate (HR), rating of perceived exertion (RPE), and technical actions between 2 soccer small-sided games (SSGs; 3 × 3 and 4 × 4) in 3 game type constraints (when playing only offense [OFF], playing only defense [DEF], and both situations [GAME]). Sixteen high-level young male players were analyzed (age 15.75 ± 0.45 years; height 172.4 ± 4.83 cm; body mass 64.5 ± 6.44 kg; HRmax199.1 ± 9.08 b/min; and 8.06 ± 1.98 years of soccer practice). All tasks were performed in 4 periods of 4 minutes interspersed with 2 minutes of active recovery. The HR was measured continuously and then analyzed by the time spent into 4 training zones according to individual %HRmax (zone 1 <75%; zone 2 75-84.9%; zone 3 85-89.9%; and zone 4 ?90%). Results identified that players were most frequently in zones 2 and 3. The 3 × 3 SSGs elicited higher HR and RPE and the most intense situation was GAME. Despite the known higher frequencies from technical actions in SSGs with fewer players, player effectiveness in 3 × 3 and 4 × 4 was identical. The use of GAME, OFF, and DEF game type constraints should be carefully planned. Using the 3 × 3 format seems more adequate when aiming for aerobic performance optimal effects; however, DEF situations should only be used to promote aerobic recovery effects. The inclusion of an additional player in SSGs had different interactions in game type constraints, and only GAME presented adequate intensity.